Some Remarks on the Weak Interaction of Mean and Turbulent Fields of Temperature and Wind Velocity - A.K. Chakraborty; H.P. Mazumdar; L.N. Persen (Engineering Transactions, 1985)
Some spectral characteristics of the kinetic energy spectrum E (x) corresponding to the case when interaction between the vorticities of the main and turbulent motions is weak and b = (du/dz)2 -ab(dT/dz) can be treated as a small nonzero parameter, are examined with the help of a perturbation method as an alternative approach.